Perspectives on Student Affairs in South Africa (African Minds, 2023)
The goal of Perspectives on Student Affairs in South Africa is to generate interest in student affairs in South Africa. The papers contained herein are based on best practice, local experience and well-researched international and local theories. The papers in this book deal with matters pertaining to international and national trends in student affairs: academic development, access and retention, counselling, and material support for students coming from disadvantaged backgrounds. They are linked to national and international developments, as described in the first two papers. This publication will assist both young and experienced practitioners as they grow into their task of developing the students entrusted to them. All contributors are South Africans with a great deal of experience in student affairs, and all are committed to the advancement of student affairs in South Africa. The editors are former heads of student affairs portfolios at two leading South African universities.